Acute kidney injury - Turan, Gulcan Bahcecioglu (Nova Science Publishers, Inc., 2023)
Acute kidney injury is a sudden and rapid deterioration of kidney function that typically develops over hours to days. Acute kidney injury remains a major public health problem in the world. Recovery from acute kidney injury is highly variable and depends on the failure of other organ systems. During treatment, the patient and family should be supported with care and education. The nurse should identify the patient's needs and plan interventions to improve the patient's quality of life. © 2023 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Acute kidney injury; Kidney; Nursing